(3cJGH CHfjI GdCSeGA hGdCaYGd hGdMQhas - (3eMeO Hf GdMSf Hf YHjO Gddg Hf ePML GdRHjOj GdCfOdSj GdETHjdj, CHh HcQ , J (B379 (3g` s; (3SjHhjg , YeQh Hf YKeGf Hf bfHQ GdMGQKj, SjHhjg,J (B180 (3g` s
(3ChdgG (B:s
(3GdMeO ddg HGRF GdGfGe heLRd GdGbSGe aEfi QCjJ YdeGA GdfMh ai ReGffG gPG heG bGQHg bO CcKQhG GdJCdja ajg hGWGdhG Gdbhd Ydi eYGfjg hbO cGf jfHZi def ge HPdc efge Gf jJUaM cJGH SjHhjg s
(3BNQgG (B:s
(3GdMOGQi LeY MOOjg hgj GdGQV GdZdjXI bGd gPG BNQ eG hLOJg ef GdGHfjI s
(3GdfSNI HgG MhGTs
(3HgG ebGHdIs
(3hgj GHfjI cJGH SjHhjI s
(3Ydjg JUMjM HGdeWGdYI s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdfMhs